English in China's universities today: The practice of English-medium instruction in China's universities is dramatically altering the linguistic nature of students' educational as well as their personal lives. (5th February 2014) - Botha, Werner
Abstract : According to Bolton (2013), Chinese university students are invariably multilingual, not only acquiring English at school, but increasingly outside of their formal curricula, through the Internet, music, computer games, movies, and television series. Indeed, many of these students are also highly mobile, and in most cases migrate throughout Greater China (and abroad) in order to pursue higher education degrees. Bolton (2012, 2013) also points out that current theorizing about English in Greater China needs to take into account what he calls 'the language worlds' of these young people, especially with regard to how they use various languages in various aspects of their lives, increasingly sampling different 'worlds', both 'physical' as well as 'imaginary' (see also Blommaert, 2010). Studies of migration and mobility within Greater China – particularly with regard to how this relates to the use of English in the context of local languages and language varieties – have received very little attention. This paper aims to fill this gap by providing a sociolinguistic account of the contemporary use of English in China's higher education, by specifically reporting on a recent large-scale sociolinguistic study that was carried out in Macau and Guangzhou, in southern China. The study reported on in this paper captures the increasing use of English as a medium (or additional medium) of instruction in two universities at these locations. The study also reveals how English is used in the personal lives of ordinary Chinese students.